An E-Book Building Methodology Using An Extensible Personalization Structure For Operationalizing E-Book Interface Metaphors - Hameed, M. Noorul (2010)
In order to address these problems, this thesis aims to identify requirements of personalization elements, to represent e-book personalization, to formalize e-book personalization components, and to develope-book packaging control and standards.Untuk menangani masalah-masalah ini, tesis ini bertujuan mengenal pasti keperluan elemen pemperibadian, untuk memperwakilkan pemperibadian e-book, untuk memformalkan komponen pemperibadian e-book, dan membangunkan pakej kawalan dan piawaian e-book.